THE IMPLEMENTATION OF STUDENT WORKSHEET MODEL IN ASSESSING TEACHER QUALITY BASED ON CURRICULUM 2013 - MIA NURKANTI; YUSUF IBRAHIM; CITA TRESNAWATI (Sriwijaya University Learning and Education International Conference, 2016)
The research is a part of a three-year research; it was the implementation stage of the complete research. It employed Educational Research and Development (R&D) design, which was modified in several features. The main objective of the research was to produce a comprehensive student worksheet which focuses on scientific project referring to the implementation of Curriculum 2013. The instruments used in the research were cognitive skill test, scientific attitude scale, observation sheet and interview. The implementation stage of the research utilized inquiry-based worksheet that was integrated with Animal Physiology subject, problem-based-learning (PBL) worksheet which was associated with Animal Ecology course, and project-based learning (PjBL) worksheet which was merged with Biotechnology subject. The research involved 60 students of Biology Education Department of Unpas from academic year 2013-2014. 30 of them were the control group and the rests were experimental group. The research shows that there is a difference in terms of students’ cognitive skill of the two groups. The cognitive skill of students in control group has an average of 2,47 (fair) and that of the experimental group is 3,56 (very good). The analysis on scientific attitude scale also shows a difference in terms of students’ affective skill: the control group’s average on this aspect is 2,70 and experiment group’s is 3,56 (very good). Assessment on students’ psycho-motor skill also presents similar trend as the control group’s average is 2,67 (good) and that of experiment group is 3,83 (very good). The averages differences of the observed skills are supported by the data from statistical average comparison test–with the level of significance of α = 0,05–which shows that the differences are significant. From the statistical data, it can be concluded that the model of learning which employs LKS is potential to provide students real experiences of scientific processes in the future, namely observation process that is problem-solving oriented. The ability to do the process in various projects can improve students thinking, which later leads to better attitudes.